“Huoling Shengji granule” for amyotrophic lateral sclerosis: protocol for a multicenter, randomized, double-blind, riluzole parallel controlled clinical trial - Liu, Xiaolu; Qin, Tingting; Li, Tao; Shan, Lei; Lei, Xiang; Xu, Xin; Wen, Bin; Feng, Yi; Yin, Ping; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2023)
Background: There is still a large demand for effective treatments to delay disease deterioration in amyotrophic lateral sclerosis (ALS). Typical symptoms of ALS are considered “flaccidity syndrome” in traditional Chinese medicine (TCM). Huoling Shengji Granule (HLSJ) is a TCM formula used to treat flaccidity syndrome. Results of preclinical tests and a previous clinical study support HLSJ as a novel drug for ALS patients. This trial proposed to examine whether a 48-week course of HLSJ is effective and safe for ALS patients diagnosed with the Chinese medicine syndrome of spleen qi insufficiency and kidney yang deficiency. Methods and analysis: In this phase II, multicenter, randomized, double-blind, riluzole parallel-controlled, superiority-design study, eligible participants had the equal opportunity to be assigned to receive either HLSJ or riluzole randomly. Eleven specialized ALS centers in Mainland China will recruit 144 patients for this trial. The primary and secondary outcomes included the change in the ALSFRS-R score and the Rasch-Built Overall Amyotrophic Lateral Sclerosis Disability Scale (ROADS) from baseline to Week 48. Discussion: Here, we endeavored to evaluate TCM for ALS using a standard evidence-based approach for the first time. In addition, the ROADS, a self-report linear-weighted questionnaire, was selected as a secondary outcome measure. We expect to offer a new reference for the outcome evaluation of ALS trials. Clinical trial registration: Chictr.org.cn (Chinese Clinical Trial Registry), ChiCTR2100044085.